The Influence of Career Development, Work Motivation, and Work Competency on Employee Performance at Rooms Inc Hotel Semarang - ANWAR, WAHYU DARIL; Rauly Sijabat; Ika Indriasari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Performance is the result of an employee carrying out important tasks and responsibilities in quality and quantity in accordance with his responsibilities. Performance is influenced by several factors to achieve the goals and objectives of an organization or company within a certain period of time. This research uses quantitative methods with a population of 70 employees at Rooms Inc Hotel Semarang using a Likert scale questionnaire with answers with a score of 1-5. This research aims to determine the results of the influence of career development, work motivation and work competency on employee performance. Calculated with several test results including: validity test, reliability test, description analysis test, multiple analysis test, f test or simultaneous test and t test or partial test